Application of mathematical models in stock market analysis - Danilenko, Svetlana (Lietuvos matematikos rinkinys, 2021)
This paper describes several methods for modulating of the stocks volatility through use of variance, EWMA and GARCH models. Results are presented using logarithmic return of the Lithuanian OMXV index.